(untitled) (Annals of Medical Research, 2023)
Aim: The aim of this study is to assess the olfactory bulb volume (OBV) and olfactory sulcus depth (OSD) in Hashimoto’s Thyroiditis (HT) patients and control group patients and comparing the measurements between two groups with 3T MR. Materials and Methods: Cranial MRI examinations of a total of 210 patients, 105 patients in the HT group and 105 patients in the control group, were evaluated retrospectively. Right, left, OBV and OSD were calculated from coronal T2W images. Results: Patients mean age was 43.74 ± 12.4 years. The mean OBV was measured as 88.57 ± 8.4 mm3 in HT patients and 93.43 ± 8.3 mm3 in control patients. The mean OSD was 8.35 ± 0.69 mm in HT patients and 8.65 ± 0.66 in control patients. Left, right, mean OBV and OSD were significantly lower in HT patients than in the control group. Conclusion: HT patients are under risk of decreased OBV and OSD, which can affect olfactory functions. This can affect the quality of life.